2019
DOI: 10.1111/1467-9566.12883
|View full text |Cite
|
Sign up to set email alerts
|

Professional autonomy and surveillance: the case of public reporting in cardiac surgery

Abstract: Professional autonomy has come under greater scrutiny due to managerialism, consumerism, information and communication technologies (ICT), and the changing composition of professions themselves. This scrutiny is often portrayed as a tension between professional and managerial logics. Recently, medical autonomy has increasingly been shaped in terms of transparency, where publication of clinical performance (via ICT) might be a more pervasive form of surveillance. Such transparency may have the potential for a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
8
1
2
Order By: Relevance
“…On a general level, such limited influence might have implications for the contents of work schedules that are developed for medical work. As such our finding does not confirm recent suggestions about an assimilation of the managerial logic into a professional logic (Exworthy et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…On a general level, such limited influence might have implications for the contents of work schedules that are developed for medical work. As such our finding does not confirm recent suggestions about an assimilation of the managerial logic into a professional logic (Exworthy et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Others have also reported that the registration burden is perceived as taking time away from patient care 24,45 and found resistance to quality registrations. 46 This reasoning might also explain the reluctance to register observed in our study. In addition, our findings suggest that external regulations (in our case mandatory quality registrations perceived as unreasonable) reduces the intrinsic motivation of healthcare professionals.…”
Section: Discussionmentioning
confidence: 68%
“…17 If compliance in gathering patient outcomes is poor, there is a risk that a registry could be used as surgeon surveillance instead which in turn may lead to higher-risk cases being avoided. 18 …”
Section: Discussionmentioning
confidence: 99%